Evaluation of the accuracy of panoramic radiograph in determining the location of the lingula - Ehsan Moudi; Mohammad Mehdizadeh; Sina Haghanifar; Maryam Sheikhi; Ali Bijani (Babol University of Medical Sciences, 2013)
Introduction: The purpose of this study was to determine the accuracy of panoramic radiograph in locating the position of lingula as an index to estimate the location of mandibular foramen. Methods: The distance measurement in this study was carried out on 30 dry mandibles, composed of at least 2 first molars and one canine. Photography and panoramic radiography of the mandible was performed in a steady reproducible position. 10 lines (including 2 horizontal and 8 vertical) were drawn from the lingula to the anterior and posterior borders of ramus, the coronoid process and the lower border of the mandible. These lines were measured and compared in photographs and panoramic radiographs. The data were analyzed using SPSS 20 software, paired t-test, Pearson correlation and linear regression analysis. Results: Considering all different distances, there was no significant difference between the findings of panoramic radiographs and photographs with regard to 3 indices as follows: cd (posteroinferiormostpoint of mandibular foramen to the posterior border of the mandible); ln (5 mm behind the postero inferior most point of mandibular foramen to the lower border of mandible) gh( 5 mm ahead of superior most point of mandibular foramen to the coronoid notch). Whereas, a significant difference was observed in other indices. Conclusions: It seems that the Panoramic radiograph is an inaccurate guide to display the precise location of the lingula.